POTENSI PENURUNAN EMISI GAS RUMAH KACA PADA PENGELOLAAN KOTORAN HEWAN SAPI MELALUI PEMBERIAN PAKAN TAMBAHAN - Ali Pramono (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2016)
On the integration of crop-livestock systems, waste biomass is used as feed for livestock. Low feed quality may increase emissions of greenhouse gases (GHG). Therefore, to reduce emissions from livestock sector is to improve the quality of animal feed. The purpose of this study was to obtain additional information about the effect of feeding (silage, hay ammoniation and UMMB) against greenhouse gas emissions from cattle manure in crop-livestock integration system. The experiment was conducted at the experimental field of Indonesia Agricultural Environment Research Institute (IAERI/Balingtan), Pati in May-July 2014. The method used to measure the GHG emissions is close chamber method, with an interval of 10 minutes. Samples of CO2, CH4 and N2O were analyzed using gas chromatography. The results showed that treatment of conventional feeding + feed supplement could reduce GHG emissions as 19 % compared to a conventional feeding. GHG emissions from animal manure fed conventional feed of 9.13 kg/head/year, whereas with conventional feed + additional feed of 7.39 kg/head/year.